Fuzzy bag models - Forkel, Hilmar (Physics letters, 2000)
We show how hadronic bag models can be generalized to implement effects of a smooth and extended boundary. Our approach is based on fuzzy set theory and can be straightforwardly applied to any type of bag model. We illustrate the underlying ideas by calculating static nucleon properties in a fuzzy chiral bag model.